2020
DOI: 10.18203/issn.2454-2156.intjscirep20204470
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and associated risk factors of human immunodeficiency virus, hepatitis B virus and syphilis among pregnant women attending Dessie referral hospital, Northeast Ethiopia

Abstract: <p><strong>Background</strong>: Globally the burden of human immunodeficiency virus (HIV), hepatitis B virus (HBV) and syphilis infections are a common problem of pregnant women where the complications are transmitted to their new born infants. These infections, often silent and without symptoms, can result in serious and fatal health consequences.</p><p><strong>Methods</strong>: Cross-sectional study was conducted on 384 pregnant women attending Dessie referral hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
1
5
2
Order By: Relevance
“…In the present study, the seroprevalence of HIV among pregnant women was 5.3%, which is in line with studies done in Cameroon (5.0%) [ 23 ], sub-Saharan African countries (5.3%) [ 24 ], and Ethiopia (5.74%) [ 6 ]. This finding was lower than the previous studies done in China (6.6%) [ 25 ], Cameroon (13.1%) [ 26 ], Gondar (11.2%) [ 27 ], and Dessie (6.5%) [ 21 ]. However, it is higher than a study done in Addis Ababa (4.8%) [ 6 ], Gondar (4.1%) [ 28 ], Sudan (1.13%) [ 29 ], Guatemala (0.21%) [ 30 ], and Angola (2.6%) [ 31 ].…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…In the present study, the seroprevalence of HIV among pregnant women was 5.3%, which is in line with studies done in Cameroon (5.0%) [ 23 ], sub-Saharan African countries (5.3%) [ 24 ], and Ethiopia (5.74%) [ 6 ]. This finding was lower than the previous studies done in China (6.6%) [ 25 ], Cameroon (13.1%) [ 26 ], Gondar (11.2%) [ 27 ], and Dessie (6.5%) [ 21 ]. However, it is higher than a study done in Addis Ababa (4.8%) [ 6 ], Gondar (4.1%) [ 28 ], Sudan (1.13%) [ 29 ], Guatemala (0.21%) [ 30 ], and Angola (2.6%) [ 31 ].…”
Section: Discussioncontrasting
confidence: 71%
“…The present study demonstrated that study participants with a history of other STIs were 3.79 times more likely to be infected with HIV than those without previous history of STIs. This finding was supported by a research done in Dessie, Ethiopia [ 21 ], and Addis Ababa [ 6 ] in which the history of STIs was associated with HIV infection. This might be because STIs create ulcer on the skin and mucous membrane which in turn facilitates the acquisition of HIV infection.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations